A Single Amino Acid Substitution in STKc_GSK3 Kinase Conferring Semispherical Grains and Its Implications for the Origin of Triticum sphaerococcum. Issue 4 (14th February 2020) - Cheng, Xuejiao; Xin, Mingming; Xu, Ruibin; Chen, Zhaoyan; Cai, Wenlong; Chai, Lingling; Xu, Huanwen; Jia, Lin; Feng, Zhiyu; Wang, Zihao; Peng, Huiru; Yao, Yingyin; et al.
Abstract : Map-based cloning of a gene underlying grain shape in wheat suggests that modest genetic changes induce dramatic phenotypic variations associated with a new wheat subspecies during evolution. Abstract: Six subspecies of hexaploid wheat ( Triticum aestivum ) have been identified, but the origin of Indian dwarf wheat ( Triticum sphaerococcum ), the only subspecies with round grains, is currently unknown. Here, we isolated the grain-shape gene Tasg-D1 in T . sphaerococcum via positional cloning. Tasg-D1 encodes a Ser/Thr protein kinase glycogen synthase kinase3 (STKc_GSK3) that negatively regulates brassinosteroid signaling. Expression of TaSG-D1 and the mutant form Tasg-D1 in Arabidopsis ( Arabidopsis thaliana ) suggested that a single amino acid substitution in the Thr-283-Arg-284-Glu-285-Glu-286 domain of TaSG-D1 enhances protein stability in response to brassinosteroids, likely leading to formation of round grains in wheat. This gain-of-function mutation has pleiotropic effects on plant architecture and exhibits incomplete dominance. Haplotype analysis of 898 wheat accessions indicated that the origin of T . sphaerococcum in ancient India involved at least two independent mutations of TaSG-D1 . Our results demonstrate that modest genetic changes in a single gene can induce dramatic phenotypic changes.